Examining Overdose and Homelessness as Predictors of Willingness to Use Supervised Injection Facilities by Services Provided Among Persons Who Inject Drugs - Kenney, Shannon R. (Am J Addict, 2020)
BACKGROUND: Internationally, supervised injection facilities (SIFs) have demonstrated efficacy in reducing rates of overdose and promoting entry into treatment among persons who inject drugs (PWID); however, they remain unavailable in the US. Early findings examining American PWID illustrate high overall willingness to use SIFs. OBJECTIVES: The current study expands upon this research by examining PWID’s likelihood to use SIFs based on services offered (e.g., provides clean needles, linkage to treatment programs) and whether known risk factors (prior overdose, homelessness) influence PWID’s willingness to use a SIF. METHODS: Participants (n = 184) were patients entering short-term inpatient opioid withdrawal management in Massachusetts between May 2018-February 2019 who reported injection drug use in the prior 30 days. We examined PWID’s likelihood to use a SIF if eight unique services were available, and compared if this differed by overdose history and homelessness status using ordered logistic regression and Pearson χ(2) – tests of independence. RESULTS: Participants (34.2 (± 8.3 sd) years of age, 68.5% male, 85.9% White, 8.2% Hispanic) reported being most likely to use SIFs that provided safety from police intervention (86.7%), entry into withdrawal management (85.9%), or clean needles (83.2%). Drug works disposal and safety from police were particularly important for PWID with a history of overdose. CONCLUSIONS: Overall, treatment-seeking PWIDs reported greater willingness to utilize SIFs if particular services were provided. SCIENTIFIC SIGNIFICANCE: These findings point to features of SIFs that may enhance treatment-seeking PWID’s amenability to utilizing these services if such sites open in the US.